Effects of vibration on natural convection in a square inclined porous enclosure filled with Cu-water nanofluid - Sayyou, Hamza; Belabid, Jabrane; Öztop, Hakan Fehmi; Allali, Karam (Emerald Group Publishing Ltd, 2024)
PurposeThe purpose of this paper is to investigate the effects of gravitational modulation on natural convection in a square inclined porous cavity filled by a fluid containing copper nanoparticles.Design/methodology/approachThe present study uses a system of equations that couple hydrodynamics to heat transfer, representing the governing equations of fluid flow in a square domain. The Boussinesq-Darcy flow with Cu-water nanofluid is considered. The dimensionless partial differential equations are solved numerically using finite difference method based on alternating direction implicit scheme. The cavity is differentially heated by constant heat flux, while the top and bottom walls are insulated. The authors examined the effects of gravity amplitude (lambda), vibration frequency (sigma), tilt angle (alpha) and Rayleigh number (Ra) on flow and temperature.FindingsThe numerical simulations, in the form of streamlines, isotherms, Nusselt number and maximum stream function for different values of amplitude, frequency, tilt angle and Rayleigh number, have revealed an oscillatory behavior in the development of flow and temperature under gravity modulation. An increase of amplitude from 0.5 to 1 intensifies the flow stream (from |psi max| = 21.415 to |psi max| = 25.262) and improves heat transfer (from Nu = 17.592 to Nu = 20.421). Low-frequency vibration below 50 has a significant impact on the flow and thermal distributions. However, once this threshold is exceeded, the flow weakens, leading to a gradual decrease in heat transfer rate. The inclination angle is an effective parameter for controlling the flow and temperature characteristics. Thus, transitioning the tilt angle from 30 degrees to 60 degrees can increase the flow velocity (from 22.283 to 23.288) while reducing the Nusselt number (from 16.603 to 13.874). Therefore, by manipulating the combination of vibration and inclination, it is founded that for a fixed frequency value of sigma = 100 and for increased amplitude (from 0.5 to 1), the flow intensity at inclination of 60 degrees is boosted, and an increase of the heat transfer rate at inclination of 30 degrees is also observed. Convective thermal instabilities may arise depending on the different key factors.Originality/valueTo the best of the authors' knowledge, this study is original in its examination of the combined effects of modulated gravity and cavity inclination on free convection in nanofluid porous media. It highlights the crucial roles of these two important factors in influencing flow and heat transfer properties.
Keywords: Heat transfer; Porous cavity; Nanofluid; Inclination angle; Vibration; Gravity modulation